Persepsi Pemahaman Mahasiswa Pendidikan Jasmani terhadap Gaya Mengajar pada Masa Kurikulum Merdeka Belajar - Maryadi, Maryanus Yadi; Juliantine, Tite; Rahmat, Alit (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the perception of the understanding of physical education students, especially as prospective physical education teachers, regarding teaching styles, both reproductive and productive styles, during the independent curriculum period. This research is quantitative descriptive research that uses a questionnaire. The research instrument is a questionnaire containing a list of questions in the form of a Likert scale, which has been tested and declared valid and reliable with (r = 0.785). The research sample was 40 PJKR Indonesian Education University students, class of 2021, using cluster sampling techniques. Based on the research results, it was concluded that the perception of physical education students' understanding of the reproductive teaching style was more pessimistic. In contrast, the perception of the productive teaching style was more positive in the independent learning curriculum. A productive teaching style emphasizes more student-centered learning to improve students' cognitive, affective, and psychomotor aspects. In conclusion, when a prospective teacher already has a good perception of the teaching style, he is expected to effectively realize relevant learning objectives according to the independent learning curriculum. Keywords: independent curriculum, perception of understanding, physical education, teaching style, physical education teacher